2018
DOI: 10.1080/10400435.2018.1467513
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary evaluation of a new anatomically based prosthetic alignment method for below-knee prosthesis

Abstract: The objectives of current study were to a) assess similarities and relationships between anatomical landmark-based angles and distances of lower limbs in unilateral transtibial amputees and b) develop and evaluate a new anatomically based static prosthetic alignment method. First substudy assessed the anthropometrical differences and relationships between the lower limbs in the photographs taken from amputees. Data were analyzed via paired t-test and regression analysis. Results show no significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…24 In the primary studies, although 10 m of self-selected walking speed for amputees to adapt alignment changes between trials was considered, adaptation time for 19 studies was not reported. The rest of the studies offered an adaptation time ranging from 5 to 30 min, 25,26,29 one study checked the prosthetic alignment after 1 month, 21 and another followed up monthly for 2 years. 24 A qualitative measure that assists prosthetists throughout the alignment process was not found.…”
Section: Resultsmentioning
confidence: 99%
“…24 In the primary studies, although 10 m of self-selected walking speed for amputees to adapt alignment changes between trials was considered, adaptation time for 19 studies was not reported. The rest of the studies offered an adaptation time ranging from 5 to 30 min, 25,26,29 one study checked the prosthetic alignment after 1 month, 21 and another followed up monthly for 2 years. 24 A qualitative measure that assists prosthetists throughout the alignment process was not found.…”
Section: Resultsmentioning
confidence: 99%
“…There were also reports of issues relating to access to prosthetic components, which prevented the prosthetist from testing and trialing a range of liners, for example. (12). "Other" items included rough alignment, review of fit and alignment, inspection of stump/palpation, funding, ordering componentry, and additional consultations (initial and follow-up after fitting).…”
Section: Part 2: Workflow and Socket Fit Issues And Managementmentioning
confidence: 99%
“…11 Others may also indirectly exacerbate fit problems later in the process, for example, suboptimal alignment, which may lead to unintended forces being transferred to the limb. 12 Prosthetists' experiences of the prosthetic manufacturing workflow, common management strategies, and their perceptions of how various steps may contribute to socket fit problems are currently undocumented. Furthermore, innovative technologies to assist in these processes and improve the socket fitting process are emerging all the time 7 but few studies have sought to explore prosthetistidentified priorities for future workflow intervention (eg, via improved methods, assessment tools, or technologies).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations